2020
DOI: 10.1186/s12888-020-02913-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level assessment of obsessive-compulsive disorder (OCD) reveals relations between neural and neurochemical levels

Abstract: Background While considerable progress has been made in exploring the psychological, the neural, and the neurochemical dimensions of OCD separately, their interplay is still an open question, especially their changes during psychotherapy. Methods Seventeen patients were assessed at these three levels by psychological questionnaires, fMRI, and venipuncture before and after inpatient psychotherapy. Seventeen controls were scanned at comparable time intervals. First, pre/post treatment changes were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Neurochemical changes such as neurotransmitter imbalance, apoptosis, oxidative damage, and inflammation of neuronal cells are significant causes of the onset of compulsive-like behavior [4,87]. While there is no direct evidence for the role of the Smo-Shh agonist PUR in treating OCD, it can show a protective effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurochemical changes such as neurotransmitter imbalance, apoptosis, oxidative damage, and inflammation of neuronal cells are significant causes of the onset of compulsive-like behavior [4,87]. While there is no direct evidence for the role of the Smo-Shh agonist PUR in treating OCD, it can show a protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in the corticostriatal-thalamocortical (CSTC) circuit and neurochemical changes have been associated with these behavioral changes [3]. In a number of investigations, researchers found that OCD patients had higher levels of dopamine and lower levels of serotonin and growth factors such asBDNF compared to healthy people [4]. Reversing these neurochemical alterations can help treat and manage OCD.…”
Section: Introductionmentioning
confidence: 99%
“…Although evidence exists that psychotherapy is able to change brain function ( Schiepek et al, 2013 , Schiepek et al, 2011 , Viol et al, 2020 ), neuroscience research has only marginally been able to give specific recommendations about how to improve the treatment of psychiatric disorders ( van den Heuvel, 2015 ), because neither psychotherapy nor medication can directly alter the activity of specific brain regions, or specific connections between regions. In contrast, our findings provide the recommendation for psychotherapy to increase flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Second-generation neuroleptics such as Risperidone and Aripiprazole can potentiate the therapeutic effect in improving the insight in some patients, although their effectiveness in treating refractory OCD patients ranges from 40 to 55% (Albert et al ., 2016 ). Moreover, structural abnormalities (Zhong et al ., 2019 ) and altered functional connectivity (Viol et al ., 2020 ; Yang et al ., 2015 ) in related brain areas partially restored in OCD patients after treatment. This suggests that OCD treatment not only ameliorates symptoms but also affects the neurophysiology of relevant brain areas.…”
Section: Relationship Between Insight and Treatmentmentioning
confidence: 99%